Two ways to display: male hummingbirds show different color-display tactics based on sun orientation. (13th March 2018) - Simpson, Richard K; McGraw, Kevin J
Abstract : Male broad-tailed hummingbirds use 2 different courtship-display tactics to show off their iridescent throat coloration based on how they orient to the sun. Some males tended to face the sun while courting females, creating a flashy color-display, while others tended to not face the sun, making them appear consistently colorful. The males with flashier displays were better able to maintain their orientation toward females, while males who appeared more consistently colored had larger throat patches. Abstract: Animals exhibit a diversity of ornaments and courtship behaviors, which often co-occur and are used for communication. The sensory drive hypothesis states that these traits evolved and vary due to interactions with each other, the environment, and signal receiver. However, interactions between colorful ornaments and courtship behaviors, specifically in relation to environmental variation, remain poorly understood. We studied male iridescent plumage (gorgets), display behavior, and sun orientation during courtship flights (shuttle displays) in broad-tailed hummingbirds ( Selasphorus platycercus ), to understand how these traits interact in both space and time to produce the perceived coloration of males. We also tested how gorget coloration varies among males based on their plumage, behavioral, and morphological characteristics. In contrast with previous work on other animals, we found that displaying males did not directionally face the sun, but instead displayed on a continuum of solar orientation angles. The gorgets of males who tended to face the sun during their displays appeared flashier (i.e., exhibited greater color/brightness changes), brighter, and more colorful, whereas the gorgets of males who tended to not face the sun were more consistently reflective (i.e., little color change) and had greater UV reflectance. We found that males who produced consistent colors had larger gorgets, whereas males with flashier gorgets were better able to maintain their angles of orientation toward the female. Our study illustrates how visual traits interact in complex ways with each other and the environment and how males of the same species can use multiple tactics to dynamically display their coloration.